PERENCANAAN LABA UMKM BUBUR AYAM PASUNDAN - Tahol, Triana Olivia; Putri Azizah Fitriyah Maharani; Maghfiroh, Hikmatul; Adiyanto, Mochamad Reza (Transpublika Publisher, 2023)
This research focuses on elucidating the intricacies of sales planning with a particular emphasis on achieving the desired profit levels through the utilization of Break Even Point (BEP) and Cost of Goods Sold (HPP) analysis. Employing a descriptive qualitative approach, this study leverages semi-structured interviews as the primary method for data collection, specifically targeting small-scale entrepreneurs as the key informants. The primary objective is to provide a comprehensive understanding of the challenges and opportunities associated with sales planning in the context of achieving optimal profit margins. The findings of this research reveal a monthly loss of -2,831,000, prompting a critical examination of the existing business model. To attain a desired income margin of 50%, it is determined that an increase in sales volume is imperative. Specifically, selling 387 portions per day at a price point of 16,986 per portion is identified as the strategic approach to offsetting losses and achieving the targeted profit margin. This insight underscores the importance of meticulous planning and strategic decision-making in the realm of sales management. Furthermore, the analysis of Break Even Point (BEP) and Cost of Goods Sold (HPP) emerges as a pivotal tool for entrepreneurs in crafting effective profit plans. The simplicity of the calculations employed in this study is highlighted as a practical advantage, enabling entrepreneurs to navigate the complexities of sales planning with relative ease.